THE BASIC PUBLIC FINANCE OF PUBLIC–PRIVATE PARTNERSHIPS. Issue 1 (15th January 2013) - Engel, Eduardo; Fischer, Ronald; Galetovic, Alexander
Abstract Public–private partnerships (PPPs) have been justified because they release public funds or save on distortionary taxes. However, the resources saved by a government that does not finance the upfront investment are offset by giving up future revenue flows to the concessionaire. If a PPP can be justified on efficiency grounds, the PPP contract that optimally balances demand risk, user‐fee distortions, and the opportunity cost of public funds has a minimum revenue guarantee and a revenue cap. The optimal contract can be implemented via a competitive auction with reasonable informational requirements. The optimal revenue guarantees, revenue sharing agreements, and auction mechanisms are different from those observed in the real world. In particular, the optimal contract duration is shorter in demand states where the revenue cap binds. These results also have implications for budgetary accounting of PPPs, as they show that their fiscal impact resembles that of public provision, rather than privatization.